Sort by
- Relevance
- |Time
The answer is r= -.5 I didn't know if you wanted the explanation or not but I...: 2r=-1 Divide 2r by both sides and the answer is r=-1/2 or -.5
2 Answers · Science & Mathematics · 14/10/2010
Simplify: (square the top and bottom of the fraction, then multiply top by R: 22.4 = 14400R/(R+139)^2 Clear fraction: (multiply both ...
2 Answers · Science & Mathematics · 21/10/2009
(1+r/m)^m (1+1/(m/r))^m (1+1/(m/r))^mr/r (1+1/(m/r))^r(m/r) as m -> infin, so does m/r (1+1/(m/r))^r(m/r) This is e^r Lets evaluate the limit mathematically...
3 Answers · Science & Mathematics · 03/12/2008
R=A + C^2 R-A= C^2 + or - sqrt(R-A) =C C=sqrt(R-A) or C=-sqrt(R-A)
2 Answers · Science & Mathematics · 30/08/2007
r is rational, so r = a / b for some integers a and b, where b is not zero...b^2 = 1 This implies b = 1 or = -1 Since r = a / b, it is the case that r = a / 1 = a or r = a / -1 = -a...
1 Answers · Education & Reference · 30/09/2011
R= 1.1926, -4.1926 Try using MathWay.com Hope this helps!
4 Answers · Science & Mathematics · 07/04/2013
The -R was the original format of the DVD created, and created... had to make the name different somehow, so the went with +R. They were originally intended for computers and not...
3 Answers · Computers & Internet · 24/07/2008
∑ _{r=1, n} 1= n ∑ _{r=1, n} r= (n+1)·n/2 ∑ _{r=1, n} r²= n·(n+1)·(2n+1)/6 ==>...2nr +r² -n -r) = (n²-n)·∑ _{r=1, n} 1 + (2n-1)· ∑ _{r=1, n} r + ∑ _{r=1, n} r² = (n²-n)·n + (2n-1)·(n...
1 Answers · Science & Mathematics · 26/07/2009
R=4x^2+8x C=x^2+2x R-C= 3x^2+6x (R-C)'= 6x+6 (R-C)"= 6 Now (R-C...
2 Answers · Science & Mathematics · 13/09/2013
|r(t)| = constant implies that 1. r(t) either doesn't change with t, r'(t)=0 or 2. its...would change also by the triangle inequality. In either case since 1. r'(t)=0 or 2. r(t) dot r'(t) = r(t)r'(t)cos(90) = 0...
1 Answers · Science & Mathematics · 17/04/2015